Text on back. Viscount B.L. Montgomery (on the left) speaks with Mrs. G. Olivier who is working on the TV set assembly-line
Text on back. Viscount B.L. Montgomery (on the left) speaks with Mrs. G. Olivier who is working on the TV set assembly-line.